Metabolic side effects of atypical antipsychotics in older adults. (25th May 2018) - Chacko, Emme; Boyd, Stephen; Murphy, Rinki
ABSTRACT: Background: The atypical antipsychotics (AAPs) are associated with a recognized class effect of glucose and lipid dysregulation. The use of these medications is rapidly increasing in elderly patients with, and without, dementia. However, the metabolic risks specific to elderly remain poorly studied. Methods: Design: A case-control study. Setting : Psychogeriatric service in Auckland, New Zealand. Participants : Elderly patients either receiving AAP treatment (cases) or not (controls) between 1 Jan 2008 and 1 Jan 2014. Main outcome measures : metabolic data of glucose, HbA1c, lipids, and cardiovascular events and death. The data were analyzed using t -tests and linear regression models for each metabolic outcome. Results: There were 330 eligible cases and 301 controls from a total study population of 5, 307. There was a statistically significant change in the HbA1c over time, within the cases group of −1.14 mmol/mol (p = 0.018, 95% CI −0.19 to −2.09). Also statistically significant was the reduction in total cholesterol of −0.13 mmol/L (p = 0.036, 95% CI −0.008 to −0.245). The only significant difference found between cases and controls was in the change in cholesterol ratio of 0.16 mmol/L between groups (95%CI 0.01–0.31, p = 0.036). Conclusions: AAP use was not associated with any clinically significant change in metabolic outcomes in this study population.